Investigating the Feasibility of Islamic Finance in Uzbekistan: Survey Results - Azamat Abdullaev; Gulnora Bekimbetova; Juliana Juliana (Review of Islamic Economics and Finance, 2023)
Purpose - This article presents the results of a survey conducted to assess the feasibility of introducing Islamic finance in Uzbekistan. The survey aimed to gather information on public opinion and awareness of Islamic finance in the country, shedding light on the opportunities and challenges associated with implementing an Islamic finance system.Methodology - The methodology involved a combination of face-to-face interviews and online questionnaires. A total of 2,235 entrepreneurs and 4,938 individuals participated in the survey, while official letters were sent to all 30 commercial banks in Uzbekistan, resulting in responses from 27 banks.Findings - The survey findings revealed a significant level of interest and demand for Islamic finance in Uzbekistan. Notably, individuals and businesses that have been hesitant to use traditional bank credit services due to religious considerations expressed a strong inclination towards Islamic finance alternatives. However, the survey also identified several challenges that need to be addressed for successful implementation. These include the absence of specific laws regulating Islamic financial products and services, the need for a tailored regulatory framework for banks operating under Islamic law, and the lack of adequately trained specialists in Islamic finance and banking.